MENINGKATKAN KREATIVITAS SISWA DENGAN PENGGUNAAN METODE EKSPOSITORI PADA MATA PELAJARAN SEJARAH KELAS XII SMAN 10 PEKANBARU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
The fact that encountered in the class in learning History shows that, there aremany students who do not have the creativity and learning competencies are still low. Based onpreliminary studies conducted by researchers that students are not creative in the followingstudy where students were pointing hand to answer questions posed by the teacher that is 12.8%and the students who pay attention to the lesson, namely 25.6%. Another fact is also foundstudents who sleepy during the learning activity that is 38.5% and 23.1% in the study bullying.One example can be seen from the daily tests of learning outcomes achieved by the class XIIScience 2nd semester 2012/2013 academic year at SMAN 10 Pekanbaru are not satisfactory asexpected.The results showed that: (1) The results of students of class XII Science SMAN 10 Pekanbaru inHistory teaching is done by using the model of expository make students more active and creativein learning. This is evident from the increasing creativity of students, in the first cycle mastery oflearning outcomes is 70.59% and (2) Results of students of class XII Science SMAN 10 Pekanbaruin History teaching is done by using the model of expository make students more active andcreative in learning. This is evident from the increasing creativity of students, in the second cyclemastery of learning outcomes is 100%.Keywords: Creativity Students, Using Expository Method.